Comments on "Case Studies in Thermal Engineering 21 (2020), 100732". (January 2023) - Awad, M.M.
Abstract: These comments indicate that the 2nd & 3rd contributions of Sgen, total have kg (s 3 K 2 m) −1 units. So, Sgen, total equation is improper. Correct expressions of Sgen, m and Sgen, f are given.